2005
DOI: 10.1007/s11270-005-6911-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropogenic activity on the Hg concentrations in the Piracicaba river basin (São Paulo State, Brazil)

Abstract: A sampling and analysis program has been completed between 1995 and 1998 in order to determine mercury concentrations in water, sediments, soils and fish in the Piracicaba river basin, one of the most populated and industrialized regions in Brazil. In sediment, the average Hg concentrations varied between 33 ± 17 ng g −1 and 106 ± 78 ng g −1 , in samples collected during the rainy and dry season, respectively. The same averages were also found for soil samples (35 ± 14 and 109 ± 61 ng g −1 ). In water, the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
0
12
1
1
Order By: Relevance
“…Among these researches, the diagnostic work on water quality in micro-basins developed by Medeiros et al [3], in the city of Americana, Daniel et al [4] and Fostier et al [5], in the Piracicaba river basin, and Moreira and Fazza [6], in the county of Limeira, near Americana city, stand out. These works showed a scenario of significant degradation of water quality, basically by discarding of domestic sewage and industrial effluent without any treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Among these researches, the diagnostic work on water quality in micro-basins developed by Medeiros et al [3], in the city of Americana, Daniel et al [4] and Fostier et al [5], in the Piracicaba river basin, and Moreira and Fazza [6], in the county of Limeira, near Americana city, stand out. These works showed a scenario of significant degradation of water quality, basically by discarding of domestic sewage and industrial effluent without any treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of fish muscle have allowed the assessment of how humans have been exposed to mercury and the evaluation of detrimental effects on animals at higher trophic levels, especially in gold mining areas (Uryu et al, 2001). The mercury concentrations reported in the edible part of the fish collected from several Brazilian freshwater environments varies from 20 ng.g -1 to 700 ng.g -1 in non-piscivorous species and from 60 ng.g -1 to 1,000 ng.g -1 in piscivorous ones (Lacerda et al, 1994;Malm et al, 1995;Lacerda, 1997;Bidone et al, 1997aBidone et al, , 1997bLebel et al, 1997;Moraes et al, 1997;Castilhos et al, 1998;Brabo et al, 1999;De Souza et al, 2000;Lechler et al, 2000;Lima et al, 2000;Leady & Gottgens, 2001;Uryu et al, 2001;Da Silva et al, 2005;Farias et al, 2005;Fostier et al, 2005). The levels of mercury in the edible part of C. gilbert, a nonpiscivorous fish, were close to the lowest values reported for Brazilian fish, suggesting that there is currently a low impact of mercury in the middle Itabapoana River food chains.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Corumbataí River, for example, many substances such as heavy metals have been detected in the water, sediments, and fish (19,20). Beside heavy metals, several classes of herbicides have been reported (21).…”
Section: Chronic Toxicity Test With C Dubiamentioning
confidence: 99%
“…Many studies of the rivers of São Paulo have been developed to identify and quantify metals in different matrices. For example, Fostier et al (20) observed that Hg contaminated all compartments (water, sediment, soil, and fish) in the Piracicaba River Basin. In the same basin França et al (37) found more than 30 elements in suspended sediments, including those of great environmental importance such as Se, Sb, Cr, Mo, Zn, and Hg.…”
Section: Limit Of Detectionmentioning
confidence: 99%